Analisis de la legislatura actual en el marco del derecho a la educacion - SANTIAGO BASALDUA, EDWING ROJER (2021)
The purpose of this research was to analyze whether the Right to Education is guaranteed in the proposed solutions to the educational problem contained in the government plans of the candidates for the presidency of the Republic in 2021. For this purpose, it was investigated by doing use of methodology with a qualitative approach, within the type of basic research and with grounded theory design; The technique of documentary analysis was used, consisting of 17 government plans carried out by the political organizations that participated in the 2021 electoral process, having found different proposals to reverse the educational problem, some of which were less coherent than others. It was concluded that the candidates representing the different political organizations offered proposals that would guarantee the Right to Education because they are focused on improving the educational system with a management that incorporates new strategies that allow access to a fundamental right of education. quality. KEY WORDS: Right to Education, Education, Government Plans.